Low back pain patients with Modic type 1 changes exhibit distinct bacterial and non-bacterial subtypes - Heggli, I.; Mengis, T.; Laux, C.J.; Opitz, L.; Herger, N.; Menghini, D.; Schuepbach, R.; Farshad-Amacker, N.A.; Brunner, F.; Fields, A.J.; Farshad, M.; Distler, O.; et al. (Osteoarthritis and cartilage open, 2024)
Modic type 1 changes (MC1) are vertebral endplate bone marrow (BM) lesions observed on magnetic resonance images in sub-populations of chronic low back pain (CLBP) patients. The etiopathogenesis remains unknown and treatments that modify the underlying pathomechanisms do not exist. We hypothesized that two biological MC1 subtypes exist: a bacterial and a non-bacterial. This would have important implications for developing treatments targeting the underlying pathomechanisms. Intervertebral disc (IVD) samples adjacent to MC1 (n ​= ​34) and control (n ​= ​11) vertebrae were collected from patients undergoing spinal fusion. Cutibacterium acnes (C.acnes) genome copy numbers (GCNs) were quantified in IVD tissues with 16S qPCR, transcriptomic signatures and cytokine profiles were determined in MC1 and control BM by RNA sequencing and immunoassay. Finally, we assessed if C.acnes GCNs are associated with blood plasma cytokines. IVD tissues from control levels had <870 ​C.acnes GCNs/gram IVD. MC1-adjacent IVDs had either “low” (<870) or “high” (>870) C.acnes GCNs. MC1 patients with “high” C.acnes GCNs had upregulated innate immune cell signatures (neutrophil, macrophage/monocyte) and pro-inflammatory cytokines related to neutrophil and macrophage/monocyte function in the BM, consistent with a host defense against bacterium. MC1 patients with “low” C.acnes GCNs had increased adaptive immune cell signatures (T-and B-cell) in the BM and elevated IL-13 blood plasma levels. Our study provides the first evidence for the existence of bacterial (C.acnes “high”) and non-bacterial (C.acnes “low”) subtypes in MC1 patients with CLBP. This supports the need for different treatment strategies.